Genomic Characterization of Fluoroquinolone-Resistant Thermophilic Campylobacter Strains Isolated from Layer Chicken Feces in Gangneung, South Korea by Whole-Genome Sequencing - Gahamanyi, Noel; Song, Dae-Geun; Yoon, Kye-Yoon; Mboera, Leonard E. G.; Matee, Mecky, I; Mutangana, Dieudonne; Komba, Erick V. G.; Pan, Cheol-Ho; Amachawadi, Raghavendra G. (MDPI, 2021)
Thermophilic Campylobacter species of poultry origin have been associated with up to 80% of human campylobacteriosis cases. Layer chickens have received less attention as possible reservoirs of Campylobacter species. Initially, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of two archived Campylobacter isolates (Campylobacter jejuni strain 200605 and Campylobacter coli strain 200606) from layer chickens to five antimicrobials (ciprofloxacin, nalidixic acid, erythromycin, tetracycline, and gentamicin) were determined using broth microdilution while the presence of selected antimicrobial resistance genes was performed by polymerase chain reaction (PCR) using specific primers. Whole-genome sequencing (WGS) was performed by the Illumina HiSeq X platform. The analysis involved antimicrobial resistance genes, virulome, multilocus sequence typing (MLST), and phylogeny. Both isolates were phenotypically resistant to ciprofloxacin (MIC: 32 vs. 32 mu g/mL), nalidixic acid (MIC: 128 vs. 64 mu g/mL), and tetracycline (MIC: 64 vs. 64 mu g/mL), but sensitive to erythromycin (MIC: 1 vs. 2 mu g/mL) and gentamicin (MIC: 0.25 vs. 1 mu g/mL) for C. jejuni strain 200605 and C. coli strain 200606, respectively. WGS confirmed C257T mutation in the gyrA gene and the presence of cmeABC complex conferring resistance to FQs in both strains. Both strains also exhibited tet(O) genes associated with tetracycline resistance. Various virulence genes associated with motility, chemotaxis, and capsule formation were found in both isolates. However, the analysis of virulence genes showed that C. jejuni strain 200605 is more virulent than C. coli strain 200606. The MLST showed that C. jejuni strain 200605 belongs to sequence type ST-5229 while C. coli strain 200606 belongs to ST-5935, and both STs are less common. The phylogenetic analysis clustered C. jejuni strain 200605 along with other strains reported in Korea (CP028933 from chicken and CP014344 from human) while C. coli strain 200606 formed a separate cluster with C. coli (CP007181) from turkey. The WGS confirmed FQ-resistance in both strains and showed potential virulence of both strains. Further studies are recommended to understand the reasons behind the regional distribution (Korea, China, and Vietnam) of such rare STs.
Keywords: ANTIMICROBIAL SUSCEPTIBILITY; JEJUNI; VIRULENCE; COLI; EPIDEMIOLOGY; PATHOGENICITY; TRANSMISSION; ANNOTATION; EMERGENCE; PROFILES